Children's visits to the paediatric intensive care unit from the nurses¿ experience - González Gil, M.T.; Alcolea Cosín, M.T.; Pérez García, S.; Luna-Castaño, Patricia; Torrent-Vela, S.; Piqueras Rodríguez, P.; Gil Domínguez RN, S.; Alonso-Lloret, F.; Belda Hofheinz, Sylvia; Sánchez-Díaz, J.I.; Espinosa Bayal, M.Á. (Elsevier, 2025)
Background: Family process disruption is one of the main consequences of the hospitalization of a critically ill child in a Paediatric Intensive Care Unit (PICU). Children's visits to PICU may help improve family coping. However, this is not a standard practice and nurses¿ experiences in facilitating children's visits to units where it is encouraged is unknown. Aim: To explore nurses¿ experience related to promoting the visits of siblings to PICU. Methods: An interpretative phenomenological study was carried out through in-depth interviews in two PICUs belonging to third level public hospitals in Madrid. Twelve nurses with more than two years of experience in PICU were interviewed. They all were working in PICU during the study. Furthermore, a PICU psychologist with an experience of four years was interviewed and this was considered shadowed data. Data analysis followed a thematic discourse analysis. Results: Nurses¿ experience of facilitating children's visits to PICU can be condensed into four themes: emerging demand for visits, progressive preparation, decision-making through common consensus and creating intimate spaces. Conclusions: The experience of nurses in facilitating visits is mainly in response to the demand of families going through prolonged hospitalisation or end-of-life situations. The role of the nurse is one of accompaniment, recognising the major role of parents in the preparation of children and in developing the visit. Nurses feel insecure and lack resources for emotional support and demand action protocols to guide intervention and decision making.